2023
DOI: 10.3390/pharmaceutics15030874
|View full text |Cite
|
Sign up to set email alerts
|

Status and Future Scope of Soft Nanoparticles-Based Hydrogel in Wound Healing

Abstract: Wounds are alterations in skin integrity resulting from any type of trauma. The healing process is complex, involving inflammation and reactive oxygen species formation. Therapeutic approaches for the wound healing process are diverse, associating dressings and topical pharmacological agents with antiseptics, anti-inflammatory, and antibacterial actions. Effective treatment must maintain occlusion and moisture in the wound site, suitable capacity for the absorption of exudates, gas exchange, and the release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 137 publications
(278 reference statements)
0
9
0
Order By: Relevance
“…Membranes are wound dressing materials that possess similar features to films. However, membranes’ ability to absorb excess exudate, keep biological fluids under pressure, maintain suitable moisture for rapid wound repair mechanism, possess effective cleaning activity, not need frequent dressing changes, and reduce the disruption of the wound bed make them interesting wound dressings for infected wounds [ 21 , 137 ]. Furthermore, membranes display excellent mechanical features, such as stretchability, softness, and flexibility [ 137 ].…”
Section: Chitosan-based Scaffolds Incorporated With Silver Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes are wound dressing materials that possess similar features to films. However, membranes’ ability to absorb excess exudate, keep biological fluids under pressure, maintain suitable moisture for rapid wound repair mechanism, possess effective cleaning activity, not need frequent dressing changes, and reduce the disruption of the wound bed make them interesting wound dressings for infected wounds [ 21 , 137 ]. Furthermore, membranes display excellent mechanical features, such as stretchability, softness, and flexibility [ 137 ].…”
Section: Chitosan-based Scaffolds Incorporated With Silver Nanoparticlesmentioning
confidence: 99%
“…The clot formation protects the wound from the invasion of exogenous agents, reduces fluid and blood loss, and offers a provisional matrix that initiates the healing process. Neutrophils and macrophages are recruited, and they secrete signaling factors that manage the next phases of the wound-healing process [21]. The second phase of the wound-healing process is inflammation, which normally overlaps with the first phase.…”
Section: The Mechanism Of the Wound-healing Processmentioning
confidence: 99%
“…As alternatives, inorganic metal NPs, such as silver, copper, and gold NPs, are extensively utilised owing to their diverse antibacterial mechanisms. 59,60 Additionally, polychitosan, honey, and fullerenes have notable antibacterial properties and biocompatibility, which circumvent the misuse of antibiotics and mitigate the risk of bacterial resistance in chronic wounds.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…It has been demonstrated that the incorporation of SLNs into gels increases drug permeability in comparison to conventional gel formulations. This has been explained by the interaction of SLNs with the stratum corneum, which leads to a longer residence time in skin layers [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%